2022
DOI: 10.3390/su14148249
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Capability and Sustainable Competitive Advantage: The Mediating Role of Ambidextrous Innovation Strategy

Abstract: After the rapid expansion of data variety, velocity and volume, human civilization experienced rapid changes in the period between the “IT” and “Data” ages. Researchers view big data and data capability as new sustainable competitive advantages that enhance the sustainability of organizational development. This paper aims to develop and empirically test a framework that will investigate how big data capability is achieved through exploitative, explorative and ambidextrous modes of innovation strategies, and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Therefore, the influencing factors of mental health of students in college English teaching courses are very important. Such factors are of great significance to the development of English teaching and the smooth progress of college students' health education [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the influencing factors of mental health of students in college English teaching courses are very important. Such factors are of great significance to the development of English teaching and the smooth progress of college students' health education [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the robust theoretical and empirical basis, it is justifiable to propose the hypothesis that the mediating role of innovative capabilities exists in the association between Big Data Analytics and data availability, and their impact on sustainable competitive advantage and organizations' performance. The presence of innovative capabilities serves as a means of connecting and enabling the conversion of data-driven insights into inventive strategies and activities, hence playing a pivotal role in determining a firm's competitive stance and overall success within the marketplace (Zhang et al, 2022). Hence, the proposition of a substantial mediating influence of innovative capabilities within the framework of this investigation is well supported.…”
Section: H2: Data Availability Has Significant Effect On Sustainable ...mentioning
confidence: 67%
“…The irretrievable nature of lost data, which was previously seen as a crucial need, emphasises the importance of optimizing data accessibility. As a result, companies endeavour to maximize the availability of their data by tackling challenges associated with data sources, volume, and collecting methodologies (Zhang et al, 2022).…”
Section: Hypothesis Devolpementmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of digital technology and the real economy is bound to bring opportunities for China's economic growth. A large number of literature research studies have shown that digital transformation has an important impact on improving productivity [1][2][3]; changing organizational and operational models [4]; enhancing corporate performance [5,6], innovation, and entrepreneurship [7][8][9][10][11][12][13][14]; and gaining a competitive advantage [15][16][17]. The equipment manufacturing industry is the engine that drives the high-quality development of China's economy.…”
Section: Introductionmentioning
confidence: 99%